Architectural Intelligence (ArcAI) Evolution and Progress on Sustainable Smartscapes Planning for the Cities of Tomorrow - Salmiah Aziz; Siti Maryam Sharun; Khairul Rijal Wagiman; Chumporn Moorapun (Environment-Behaviour Proceedings Journal, 2024)
Rapid urbanization and environmental concerns underscore the need for sustainable design in urban areas. This study delves into sustainable smart scapes, integrating eco-friendly practices and smart technologies to meet urban demands. It examines green infrastructure, renewable energy, and smart parameters’ integration, assessing their effectiveness through literature review and case studies. Exploring technologies like Internet of Things (IoT), artificial intelligence (AI), and data analytics, the research adopts qualitative methods - case studies, structured interviews, and literature review – for a nuance understanding of. It aims to inform future sustainable architecture and urban planning, emphasizing smartscapes’ role in resource optimization, economic growth, and community inclusivity, contributing to interdisciplinary knowledge advancement.
Keywords: Smart Cities and Technologies